2020
DOI: 10.33314/jnhrc.v18i3.2493
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Proton Pump Inhibitor and Triple Therapy Regimen for Laryngospharyngeal Reflux Disease

Abstract: Background: Laryngopharyngeal reflux is retrograde flow of contents of the stomach to the larynx and the pharynx. The study aims to compare two regimens (proton pump inhibitor monotherapy versus triple therapy) on the outcome of Helicobactor pylori positive laryngopharyngeal reflux disease. Methods: The presence of laryngopharyngeal reflux was determined by reflux symptom index and reflux finding score. The presence of Helicobactor pylori in the tissue was confirmed by rapid urease test. All urease test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recently, approximately 50% of patients with laryngeal cancer have gastric H. pylori infection (prevalence, 47–75%) [ 12 , 13 , 14 ]; however, some studies have suggested that gastric H. pylori infection may not play a role in the development of laryngeal cancer compared with controls [ 15 , 16 ]. H. pylori infection can induce laryngopharyngeal reflux (LPR) [ 17 , 18 , 19 ]; furthermore, gastric reflux can bring it to the larynx. Therefore, H. pylori is present in laryngeal mucosa [ 20 ] and has the potential to damage epithelial and mucosal barriers, and that the subsequent inflammatory process can lead to chronic harm and epithelial cell proliferation resulting in laryngeal pathology [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, approximately 50% of patients with laryngeal cancer have gastric H. pylori infection (prevalence, 47–75%) [ 12 , 13 , 14 ]; however, some studies have suggested that gastric H. pylori infection may not play a role in the development of laryngeal cancer compared with controls [ 15 , 16 ]. H. pylori infection can induce laryngopharyngeal reflux (LPR) [ 17 , 18 , 19 ]; furthermore, gastric reflux can bring it to the larynx. Therefore, H. pylori is present in laryngeal mucosa [ 20 ] and has the potential to damage epithelial and mucosal barriers, and that the subsequent inflammatory process can lead to chronic harm and epithelial cell proliferation resulting in laryngeal pathology [ 21 ].…”
Section: Introductionmentioning
confidence: 99%